TYPOLOGY FEATURES OF HOME TEXTILES IN MODERN INTERIOR DESIGN - Пашукова, С. Г.; Колосніченко, М. В.; Остапенко, Н. В.; Слітюк, О. О. (Art and Design, 2019)
The article concerns the research of stylistic, artistic and compositional, constructive and decorative features of home textile elements (on an example of decorative pillows) in the context of a compositional balance development of modern interior. A complex of general scientific methods has been used. They include analytical methods for studying information sources; system-based structural ones for revealing the essence of home textile products, which contributed to the definition of its individual elements typology; complex historical method for studying the origins and process of forming decor objects; visual and analytical ones for the analysis of material and technical components of decorative pillows and cultural approach. A retrospective analysis of the preconditions for the emergence, formation and development of decorative forms of textiles and pillow decoration elements has been done. The specificity of the means of their artistic expression has been studied. The existing variations of pillows and thir decorations have been analyzed and summarized. The functions of decorative pillows have been defined and their features have been revealed. On the basis of the conducted analytical research the existing varieties of modern decorative home textiles have been generalized and systematized. The features have been defined, the functions of modern decorative pillows have been structured and various signs have been distinguished. Practical significance. The information base of different types of pillows has been formed, the main and specific features have been characterized. The modern aspects of their application in the context of interior decoration and design have been revealed. The emphasis has been done on stylistic decisions and varieties of decorative design of modern pillows, and a visual range of these products has been built.